INFOGRAFIS MITIGASI BENCANA KEBAKARAN HUTAN DAN LAHAN PADA MEDIA SOSIAL PEMERINTAH DAERAH PROVINSI RIAU - Galih Perwita Rosadha (Jurnal Desain Komunikasi Visual Asia, 2022)
Fire is a type of disaster that can occur naturally and artificially. In Riau Province, forest and land fires almost always occur every year. The haze caused residents around the Riau area also affected by the haze resulting from the fire. The provincial government of Riau has carried out various mitigation activities, including the installation of printed billboards in all districts / cities in Riau, but this is still ineffective. Therefore, other forms of media were created, namely infographics that are distributed through digital media to be able to expand the reach of information and get new target recipients of information, namely the younger generation. The method used in this design is a model of the Sanyoto Ebdi sadjiman which begins with the formulation of the problem, determining objectives, analysis, synthesis to determine the media used, the design concept to the final design. This design will produce series and singles infographics which are then distributed using social media related to the main website of the Riau regional government, namely riau.go.id. It is hoped that by using the infographic media, people living in areas that are not reached by conventional print media are expected.